Chromoendoscopy versus autofluorescence imaging for neoplasia detection in patients with longstanding ulcerative colitis (FIND-UC): an international, multicentre, randomised controlled trial - Vleugels, Jasper L.A.; Rutter, Matt D.; Ragunath, Krish; Rees, Colin J.; Ponsioen, Cyriel Y.; Lahiff, Conor; Ket, Shara N.; Wanders, Linda K.; Samuel, Sunil; Butt, Faheem; Kuiper, Teaco; Travis, Simon P.L.; et al. (Elsevier, 2018)
Background: Patients with longstanding ulcerative colitis (UC) undergo regular dysplasia surveillance because of increased colorectal cancer risk. Previous studies demonstrated that autofluorescence imaging (AFI) and chromoendoscopy (CE) increased dysplasia detection. The aim of this study was to determine whether AFI should be further studied as an alternative method for dysplasia surveillance in patients with longstanding UC.